The influence of psychological characteristics of a personality on the tactics of forensic psychiatric examination - O. P. Makarova (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the influence of psychological characteristics of a personality on the tactics of forensic psychiatric examination.